A Cell-Based Metabonomics Approach to Investigate the Varied Influences of Chrysophanol-8-O-β-D-Glucoside With Different Concentrations on L-02 Cells - Liu, Meichen; Gong, Xiaohong; Quan, Yunyun; Zhou, Yimeng; Li, Yunxia; Peng, Cheng (Frontiers in Pharmacology, 2019)
In this study, the effects of different concentrations of chrysophanol-8-O-β-D-glucoside (C-8-O-β-D-glu) on L-02 liver cells were measured by high content analysis (HCA) and metabonomics to explore the potential mechanism involved. The results showed that low concentrations (12, 24 µM) of C-8-O-β-D-glu increased the cell viability significantly, while high concentration (96 µM) showed significant cytotoxicity on L-02 cells. HCA was applied to examine the changes of the nuclei and mitochondria after the cells being exposed to C-8-O-β-D-glu for 24 h. The results showed high concentration (96 µM) of C-8-O-β-D-glu significantly reduced the number of living cells, increased average nucleus area, DNA content and mitochondrial membrane potential (MMP). Then untarget metabonomics was carried out to identify potential biomarkers and metabolic pathways of L-02 cells impacted by C-8-O-β-D-glu. Eleven important potential biomarkers associated with four metabolic pathways were identified in this analysis. Remarked dysregulation of alanine, aspartate and glutamate metabolism were observed in both LCG and HCG. In addition, low concentration of C-8-O-β-D-glu would impact arginine and proline metabolism. High concentration of C-8-O-β-D-glu would impact phenylalanine metabolism and beta-Alanine metabolism. Alanine, aspartate and glutamate metabolism, arginine and proline metabolism, phenylalanine metabolism, beta-Alanine metabolism were involved in different effects of C-8-O-β-D-glu on L-02 cells.